PENGETAHUAN, SIKAP, DAN PERILAKU PEKERJA PERIKANAN TERHADAP BAHAN TAMBAHAN PANGAN (BTP) BERBAHAYA - Marnida Yusfiani; Budi Dharma (Berkala Perikanan Terubuk, 2016)
Knowledge, Attitude, and Practice (KAP) of fishery workers about forbidden food additives are explained. The study is aimed to know forbidden food additives (formaline and borax) by qualitative experiment and to conducted KAP fishery workers about adding forbidden food additives into salted fish that produce. The data were collected by using of questioner that are arranged and developed systematically. The results haved showed that 20% of salted fish processing unit (UP) produce salted fish which indicate formaline and borax. Most of fishery workers agreed that formaline and borax are forbidden and danger adding into salted fish. The side effect factors that influence adding food additives into salted fish are Attitudes, Practice, working periode, age, and education.